Analysis of Deep Learning Strategies in Indonesian Language Learning Phase D of Kurikulum Merdeka - Anisa Lidia Putri; Suci Angesti; Nia Ramadani; Helty; Liza Septa Wilyanti (Universitas Indo Global Mandiri, 2026)
The transformation of education in Indonesia through the implementation of the Kurikulum Merdeka has brought about a significant shift in the learning paradigm. The focus of learning is no longer solely on mastery of material, but rather on developing students' overall competencies. This study aims to analyze deep learning strategies in Indonesian language learning under Phase D of the Kurikulum Merdeka. The study used a qualitative approach with a content analysis of learning documents. The results indicate that the strategies identified include critical thinking, collaborative learning, communicative learning, contextual learning, project-based learning, and metacognitive reflection. Critical thinking strategies are the most dominant because they encourage students to analyze, evaluate, and interpret information. These findings indicate that Indonesian language learning under Phase D has implemented deep learning principles that are oriented towards meaningful, active, and student-centered learning. Keywords: Deep learning, Indonesian language, Kurikulum Merdeka